Adipocytes, Innate Immunity and Obesity: A Mini-Review - Blaszczak, Alecia M.; Jalilvand, Anahita; Hsueh, Willa A. (Frontiers in Immunology, 2021)
The role of adipose tissue (AT) inflammation in obesity and its multiple related-complications is a rapidly expanding area of scientific interest. Within the last 30 years, the role of the adipocyte as an endocrine and immunologic cell has been progressively established. Like the macrophage, the adipocyte is capable of linking the innate and adaptive immune system through the secretion of adipokines and cytokines; exosome release of lipids, hormones, and microRNAs; and contact interaction with other immune cells. Key innate immune cells in AT include adipocytes, macrophages, neutrophils, and innate lymphoid cells type 2 (ILC2s). The role of the innate immune system in promoting adipose tissue inflammation in obesity will be highlighted in this review. T cells and B cells also play important roles in contributing to AT inflammation and are discussed in this series in the chapter on adaptive immunity.